KARAKTERISTIK PERUSAHAAN TERHADAP TAX AVOIDANCE PERUSAHAAN REAL ESTATE - Oktavia Fara Sherly Indrasafitri; Arif Nugroho Rachman (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The purpose of this study was to know the effect of the current ratio, company size, ROA and DER on tax avodiance. This research is a quantitative research. Data collection through documentation The research population of real estate companies and properties on the Indonesia Stock Exchange in 2018-2021 totals 54 companies. Determination of the sample used purposive sampling so that a sample of 34 companies. Data analysis techniques using multiple linear regression, t test, F test and the coefficient of determination. The results showed that the current ratio has a negative and significant effect on tax avoidance. Firm size has no effect on tax avoidance. Return on assets has a negative and significant effect on tax avoidance. The debt to equity ratio has a positive and significant effect on tax avoidance